2023
DOI: 10.3390/vaccines11121801
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of and Adherence to a Four-Dose RTS,S/AS01 Schedule: Findings from a Longitudinal Qualitative Evaluation Study for the Malaria Vaccine Implementation Programme

Jessica Price,
Nikki Gurley,
Margaret Gyapong
et al.

Abstract: Background: The WHO recommended the use of the RTS,S/AS01 malaria vaccine (RTS,S) based on a pilot evaluation in routine use in Ghana, Kenya, and Malawi. A longitudinal qualitative study was conducted to examine facilitators and barriers to uptake of a 4-dose RTS,S schedule. Methods: A cohort of 198 caregivers of RTS,S-eligible children from communities where RTS,S was provided through the pilot were interviewed three times over a ≈22-month, 4-dose schedule. The interviews examined caregiver perceptions and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…This finding is similar to reports by Price et al . [ 22 ] which reported that in first three implementing countries of malaria vaccine, information barrier contributed to no or partial uptake of malaria vaccine. Additionally, in Kenya, a recent study by Hoyt et al .…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to reports by Price et al . [ 22 ] which reported that in first three implementing countries of malaria vaccine, information barrier contributed to no or partial uptake of malaria vaccine. Additionally, in Kenya, a recent study by Hoyt et al .…”
Section: Discussionmentioning
confidence: 99%